Impact Of Unfavorable Industrial Microclimate On The Human Body And Preventive Measures - N. M. Bakhriddinova (Euro Asian Journal Publishing, 2023)
The work studied the impact of an unfavorable industrial microclimate on the body and preventive measures.. The characteristics of air pollution in the working area are given. The main directions of strengthening environmental safety are widely covered.
Keywords: Microclimate; work area; production premises